2000
DOI: 10.1007/s007010070007
|View full text |Cite
|
Sign up to set email alerts
|

Central Lumbar Disc Herniation

Abstract: Postoperative outcome of central lumbar disc herniation (CLDH) is poorer as compared with other types of lumbar disc herniation. The reason seems to be the anatomical position of the disc herniation with a peculiar derangement of the disc architecture. The surgical approach itself or the subcategories of CLDH appear to have only minor impact on postoperative outcome. Interlaminar fenestrations, in general, are appropriate for removal of the disc fragments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
0
23
1
Order By: Relevance
“…Studies related to outcomes of central large herniations are a mixed bag without any emphasis on symptomatology. 1,[6][7][8] The results of discectomy in these studies are associated with a low satisfaction rate. 1,[6][7][8] This could be a result of varied inclusion criteria in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies related to outcomes of central large herniations are a mixed bag without any emphasis on symptomatology. 1,[6][7][8] The results of discectomy in these studies are associated with a low satisfaction rate. 1,[6][7][8] This could be a result of varied inclusion criteria in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,[6][7][8] Postoperative outcomes of CLDH is not only poorer than the other more common forms of disc herniation, but they also differ remarkably among different studies. 1,[6][7][8] This could be due to varied inclusion and exclusion criteria and varied treatment options, making it a mixed bag where oranges were compared with apples. Maybe there is a need for classification of patients with CLDH based on their dominant presenting symptoms and the delineation of factors associated with poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors are related to the surgeon, such as experience or the use of the microscope. [15][16][17] The emergency situation is challenging because the surgeon must decide whether it is necessary to perform the operation immediately or whether it is safe to delay surgery to perform the operation during regular working hours. It has been reported that emergency surgery can present a risk factor by itself in other surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…During surgery, patients were in the prone position and localized under a C-arm X-ray apparatus (Siemens, Berlin, Germany) (1). Body surface projections in the central line of processus spinosus of vertebra lumbalis and all horizontal lines at the upper edge of the target intervertebral disk were marked.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical symptoms of central lumbar disc herniation (CLDH) are varied (1). Pain symptoms typically occur on one or both sides of lower limbs.…”
Section: Introductionmentioning
confidence: 99%